The Role of Human Resources Motivation in the Development of Hotel Enterprises in the Ferizaj Region (Republic of Kosovo) - Ismajli, Naim; Behluli, Arbresha; Bajrami, Roberta (European Journal of Economics and Business Studies, 2018)
The main purpose of this research is to describe and sift the overall level of motivation of the employees of hotel enterprises in the region of Ferizaj, in the Republic of Kosova regarding the factors affecting it as well as measuring the relationship between motivation and quality of service. The first objective of this study is to measure and describe work relationship among the employees of hotel enterprises in the Ferizaj Region, while the second objective is to measure and describe payroll and bonuses among the employees of hotel enterprises in the Ferizaj Region. Part of the study were 467 workers of the hotel enterprises of which 36 percent ( n=171) were women, and 63.4 percent (n=296) men. Analysis of empirical data is performed using the Statistical Package for the Social Sciences (SPSS) system. From the findings of this study it has been founded that the employees of hotel enterprises in Ferizaj region are above average motivated in their work. Salary is the most important factor that has an impact on motivation, followed by the work-related relationships. However, comparing level of motivation among different places, we can see that the workers in Ferizaj and Shterpce were more motivated because more motivational techniques were used by their managers, whereas employees in Shtime and Kaqanik were less motivated. The variance analysis identified significant statistical differences in terms of motivation at work.Regarding the quality of service from the statistical data, we see that the quality of service is in right proportion to motivation. Clients were satisfied with the hotel services in general but the citizens of Ferizaj and Shterpca were more satisfied whereas citizens of Shtime and Kaqanik were less satisfied. Finally, it can be asserted that the findings of this study can help the structures of hotel establishments to use efficient techniques to motivate their employees,which could lead to the increase of the quality of service provided.
Keywords: Hotel enterprises in the region of Ferizaj, motivation, quality of service